A TRANSPORTATION MODEL FOR AN EFFECTIVE DISASTER RELIEF OPERATION IN THE SADC REGION - Baraka, Jean-Claude Munyaka; Yadavalli, Prof Sarma; Singh, Mr Ranil (The South African Journal of Industrial Engineering, 2017)
This paper reviews some challenges faced by humanitarian logistics and supply chain organisations in the transportation of resources, evacuees, and emergency supplies for disaster relief operations in the SADC region. To identify the appropriate transportation to assist in the region, three models were reviewed and proposed: A typical transportation problem, a genetic algorithm based on a spanning tree, and a linear optimisation using Excel Solver. Reviewing the literature revealed that both man-made and natural disasters have caused over ninety thousand fatalities and affected millions just over the past three decades. A further review shows that most disaster deaths are the result of poor infrastructure, especially in populated areas. This presents a challenge to relief organisations in their efforts to provide on-time relief to victims in pre- and post-disaster periods. Although each proposed transportation problem has particular complexities, each of them could assist the region to decrease the relief operation response time and cost. This paper provides the reader with a greater understanding of the challenges faced by the humanitarian supply chain in the SADC region. This paper proposes a conceptual model based on an actual empirical case.